Assessing Blue Lagoon Beach as a Special Interest Snorkeling Destination in Bali: A Qualitative Analysis of 4A Attributes, Activity Characteristics, and Management Implications - Pradnyani, Ida Ayu Ari; Wardanayasa, I Ketut; Piartha, I Nyoman (E-Journal of Tourism, 2026)
Marine tourism increasingly relies on experience-based coastal activities, and snorkeling has become one of the most accessible forms of special interest tourism in coral-reef destinations. However, the attractiveness of a snorkeling site cannot be assessed only through scenery; it also depends on destination readiness, safety, interpretation, and management capacity. This study examines Blue Lagoon Beach in Padangbai, Karangasem, Bali, with two objectives: first, to assess its feasibility as a special interest snorkeling destination through the 4A framework (attraction, amenities, accessibility, and ancillary services); and second, to analyse the characteristics of snorkeling activities and their implications for sustainable marine tourism. The study employed a qualitative descriptive design based on field observation, semi-structured interviews with local tourism actors and community stakeholders, and documentary review. Data were analysed thematically through data reduction, data display, and conclusion drawing. The findings show that Blue Lagoon possesses strong natural attractiveness, adequate tourism amenities, relatively convenient accessibility, and supporting ancillary services that make the destination operationally viable. Its snorkeling product is strengthened by calm shallow waters, local guide assistance, and learning opportunities related to reef etiquette and marine conservation. At the same time, the study indicates the need for stronger interpretive materials, visitor management, and conservation-sensitive governance to reduce ecological risk as visitation grows. The article argues that Blue Lagoon should be positioned not merely as a generic beach attraction, but as a community-based special interest marine destination whose competitiveness depends on balancing visitor experience with coral reef protection.